Implementasi Model Pembelajaran Squenced (Urutan) Dalam Meningkatkan Kemampuan Siswa Memahami Hukum Bacaan Mad pada Bidang Studi Al Quran Hadis di Kelas VII MTs. Swasta Teladan Gebang - Zaifatur Ridha; Muhammad Supawi; Fadila Munawarah (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2021)
Efforts to improve connected skills through Squenced learning models for MTs students. Teladan Gebang Private. Grade VII MTs students. Teladan Gebang Private who obtain learning by using the Squenced learning model approach shows that the understanding of the Qur'anic material of the Hadith is significantly better than that of students who get regular learning. This can be seen from the average score of the connected ability of students in the study of the Qur'anic Hadith. Connected ability of VII grade MTs students. Teladan Gebang Private can be done by applying the Learning Squenced model. There is a significant relationship between the improvement of connected skills through the Learning Squenced model in MTs. Teladan Gebang Private. The attitude of students during the learning of the Qur'an the Hadith looks good, namely students have the enthusiasm to participate in classroom learning activities, students look more enthusiastic in learning and communication activities that occur during the learning process in the classroom runs effectively, as the communication runs two directions, namely from teacher to student and vice versa from students to teachers. Activities of students who get learning using learning models Squenced is more active in learning in class and students who get the application of learning models Squenced is more active in improving students' connected skills, and also students are more daring to ask or ask questions to teachers, and be more creative in solve the problem given, so the connected ability of MTs students. Teladan Gebang Private can be improved through the application of the Squenced model.